Analisis Keterkaitan GEN BMP15, BMPR1B, dan KISS1 dengan Sifat Fekunditas pada Kambing Peranakan Etawah Betina - Rini Herlina Mulyono; Cece Sumantri; Ronny Rachman Noor; . Jakaria; Dewi Apri Astuti (Institut Pertanian Bogor, 2019)
Etawah grade goat is a result of grading up line between Kacang and Etawah goats, which well adapted to Indonesia’s humid tropical climate. This goat is a dual-purpose goat breed for milk and meat production. The objectives of this study were to evaluate the polymorphism of fecundity genes through the investigation of four candidate genes for prolificacy, i.e., BMP15 (exon 1), BMPR1B (exon 1), KISS1 (exon 1), and KISS1 (intron 1) and their associations with the litter size of Etawah-Grade does. The diversity of BMP15 (exon 1), BMPR1B (exon 1), KISS1 (exon 1), and KISS1 (introns 1) genes were analyzed by the PCR-RFLP technique. A total of 106 of DNA samples were collected from Etawah-Grade does at BPTU-HPT Pelaihari in Pelaihari, South Kalimantan (51 heads) and Cordero Farm in Bogor, West Java (55 heads). Genetic polymorphisms between the two Etawah-Grade groups were calculated as well as their allele and genotype frequencies and the Polymorphic Informative Content (PIC). The Kruskal-Wallis one-factor ranked analysis of variance was used to determine whether there was any effect of genotype of the fecundity genes on litter size. The polymorphic information content (PIC) estimated at BPTU-HPT Pelaihari was 0.313, whereas at Cordero farm was 0.174, and overall PIC was 0.244. There was no association between genotypes of BMP15 (exon 1), BMPR1B (exon 1), KISS1 (exon 1), and KISS1 (intron 1) genes and litter size. Results indicated that BMP15 (exon 1) and KISS1 (exon 1) genes were monomorphic. However, the other two loci showed polymorphisms. The BMPR1B (exon 1) locus had two genotypes with the frequency for CC (96.23%) and for GG (3.77%), and KISS1 (intron 1) locus had three genotypes with the frequency for TT (80.19%), AT (17.92%), and AA (1.89%).